Bimetal (Fe/Zn) doped BiOI photocatalyst: An effective photodegradation of tetracycline and bacteria. (October 2021) - Talreja, Neetu; Afreen, Shagufta; Ashfaq, Mohammad; Chauhan, Divya; Mera, Adriana C.; Rodríguez, C.A.; Mangalaraja, R.V.
Abstract: Tetracycline (TC) is one of the most commonly used broad-spectrum antibiotics to treat the bacterial infection. TC antibiotics enter into the environment because of partial metabolism in the humans and animals, thereby increasing the environmental toxicity. Therefore, it is highly needed to treat TC antibiotics from the water system. In this aspect, the present work focus on the synthesis of Fe and Zn (bimetal) incorporated with different concentrations into the bismuth-oxy-iodide (Fe/Zn–BiOI) based photocatalyst materials. The synthesized Fe/Zn–BiOI was tested against photocatalytic degradation of TC antibiotics and bacteria. The band gap value of the synthesized Fe/Zn–BiOI was calculated 2.19 eV. The incorporation of the Fe and Zn metals within the BiOI aided advantages that increased the reactive sites, oxygen defects, photon adsorption, production of hydroxyl radicals, and decrease the recombination rate, thereby high photo-degradation ability. The maximum degradation of 83% was observed using Fe/Zn–BiOI-1-1 at 10 mg/L of TC antibiotics concentration. Moreover, 98% of degradation was observed at pH 10 of the TC antibiotics. The photo-activity against bacteria of the Fe/Zn–BiOI was also determined. The data suggested that the synthesized Fe/Zn–BiOI based photocatalyst materials effectively inhibited the bacterial strains. Therefore, Fe/Zn–BiOI based photocatalyst materials might be promising materials that effectively degrade TC antibiotics as well as bacteria. Highlights: Bimetal (Fe–Zn)–BiOI nanostructure photocatalytic materials are synthesized. The incorporation Fe and Zn metal increase the oxygen defects and create heterjunction. The Fe–Zn–BiOI might be promising material for the photodegradation.